Hidden Curriculum Sebagai Penguatan Budaya Kearifan Lokal dalam Pembelajaran PAI di SMPN 7 Sinjai - Nurhayati, R.; Nur, Makmur Jaya; Suwito, Agus; Ningsih, Diarti Andra; Ramadani, Nuriya; Jannah, Miskatul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
The implementation of hidden curriculum to strengthen local wisdom culture in Islamic Religious Education (PAI) is a crucial step to help students understand and apply noble cultural values, while also fostering their holistic development. This study aims to describe the forms and roles of hidden curriculum in strengthening local wisdom culture in PAI learning at SMPN 7 Sinjai. A qualitative approach was used, with data collected through observation, interviews, and documentation from relevant sources. The analysis focused on understanding how hidden curriculum supports local wisdom in PAI. The findings indicate that the hidden curriculum at UPTD SMPN 7 Sinjai plays a significant role in reinforcing religious habits and behaviors aligned with Islamic teachings and local cultural traditions. Forms of hidden curriculum include the internalization of norms, social values, and teaching behavior embedded in cultural practices such as mapatabe’ and papaseng, incorporating Bugis language lessons, promoting environmental awareness, and encouraging cleanliness. Additionally, religious habits are nurtured through congregational prayers to develop empathy and togetherness, extracurricular tahsin activities, Qur'an literacy programs, and dhuha prayers. These elements reflect the integration of local wisdom and religious values in shaping students’ character through hidden curriculum practices.